Extravascular fibrinogen in the white matter of Alzheimer's disease and normal aged brains: implications for fibrinogen as a biomarker for Alzheimer's disease. (29th January 2019) - McAleese, Kirsty E.; Graham, Sophie; Dey, Madhurima; Walker, Lauren; Erskine, Daniel; Johnson, Mary; Johnston, Eleanor; Thomas, Alan J.; McKeith, Ian G.; DeCarli, Charles; Attems, Johannes
Abstract: The blood–brain barrier (BBB) regulates cerebrovascular permeability and leakage of blood‐derived fibrinogen. Dysfunction of the BBB has been associated with cerebral arteriolosclerosis small vessel disease (SVD) and white matter lesions (WML). Furthermore, BBB dysfunction is associated with the pathogenesis of Alzheimer's disease (AD) with the presence of CSF plasma proteins suggested to be a potential biomarker of AD. We aimed to determine if extravascular fibrinogen in the white matter was associated with the development of AD hallmark pathologies, i.e., hyperphosphorylated tau (HPτ) and amyloid‐β (Aβ), as well as SVD, cerebral amyloid angiopathy (CAA) and measures of white matter damage. Using human post‐mortem brains, parietal tissue from 20 AD and 22 non‐demented controls was quantitatively assessed for HPτ, Aβ, white matter damage severity, axonal density, demyelination and the burden of extravascular fibrinogen in both WML and normal appearing white matter (NAWM). SVD severity was determined by calculating sclerotic indices. WML‐ and NAWM fibrinogen burden was not significantly different between AD and controls nor was it associated with the burden of HPτ or Aβ pathology, or any measures of white matter damage. Increasing severity of SVD was associated with and a predictor of both higher WML‐ and NAWM fibrinogen burden (all P  < 0.05) in controls only. In cases with minimal SVD NAWM fibrinogen burden was significantly higher in the AD cases ( P  < 0.05). BBB dysfunction was present in both non‐demented and AD brains and was not associated with the burden of AD‐associated cortical pathologies. BBB dysfunction was strongly associated with SVD but only in the non‐demented controls. In cases with minimal SVD, BBB dysfunction was significantly worse in AD cases possibly indicating the influence of CAA. In conclusion, extravascular fibrinogen is not associated with AD hallmark pathologies but indicates SVD, suggesting that the presence of fibrinogen in the CSF is not a surrogate marker for AD pathology.